2001
DOI: 10.1007/s004150170178
|View full text |Cite
|
Sign up to set email alerts
|

Study of binding and neutralising antibodies to interferon-? in two groups of relapsing-remitting multiple sclerosis patients

Abstract: Interferon (IFN)-beta is generally considered an effective treatment for multiple sclerosis (MS); however, some patients do not respond to this therapy, possibly due to the production of neutralising antibodies (NAB) which can prevent the biological effect of IFN-beta. We compared the two types of IFN-beta, the glycosylated IFN-beta1a and the non-glycosylated IFN-beta1b, as their chemical differences may entail differing immunogenic capacities. We studied 22 relapsing-remitting MS patients treated with IFN-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…As previously discussed, data from clinical trials suggest that the development of NAbs may reduce the therapeutic efficacy of IFNβ therapy [4,6,8]. However, there is no consensus on the immunomodulatory role of anti-IFNβ antibodies, and some authors have published findings that refute their reported antitherapeutic effect [19][20][21]. The discrepancies among the published data may be explained by differences in both methodology and numbers of patients analysed.…”
Section: Discussionmentioning
confidence: 80%
“…As previously discussed, data from clinical trials suggest that the development of NAbs may reduce the therapeutic efficacy of IFNβ therapy [4,6,8]. However, there is no consensus on the immunomodulatory role of anti-IFNβ antibodies, and some authors have published findings that refute their reported antitherapeutic effect [19][20][21]. The discrepancies among the published data may be explained by differences in both methodology and numbers of patients analysed.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, a review of the comparative trials, which used a single assay method, is necessary to critically evaluate differences in immunogenicity among IFNβs. Several studies have compared the incidence of NAbs among IFNβ products [3,6,15,23,32,37]. However, herein we review only studies that did the following: contained a reasonable number of patients, followed patients for ≥ 12 months, and controlled for the potential interference of residual IFNβ in peripheral blood after injection (blood collection occurred ≥ 36 hours after IFNβ injection).…”
Section: Comparative Studiesmentioning
confidence: 98%
“…IFN-␤ was selected as a model protein because neutralizing Ab responses develop in multiple sclerosis patients undergoing IFN-␤ therapy (15)(16)(17). The effect of neutralizing Abs on IFN-␤ efficacy is controversial (16, 18 -20).…”
Section: T He Number Of Epitope Regions Recognized Within Protein Immmentioning
confidence: 99%